2019
DOI: 10.1590/fst.11718
|View full text |Cite
|
Sign up to set email alerts
|

Mineral content, phenolic compounds and bioactive amines of cheese bread enriched with cowpea

Abstract: Cheese bread presents great acceptance and market expansion. Due to the lack of standardization in its manufacturing, various ingredients can be added. Ot was aimed to determine the content of minerals, bioactive compounds and antioxidant activity in cheese bread enriched with biofortified cowpea. Two formulations were prepared, standard cheese bread (without cowpea) and enriched cheese bread. The minerals were analyzed using the plasma emission spectrometry technique with inductive coupling, phenolic compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…Another study discovered that cheese bread containing cowpeas had higher levels of condensed tannins, flavonoids, and total phenolic content. These results also align with the increase in antioxidant activity, which reached 497.5 and 731 µmol TEAC/100 gr using the DPPH and ABTS free radical scavenging methods [23] In addition, the components of the Maillard process in the crust increase the activity of bread. The antioxidant qualities of bread products can be impacted by phenolic compounds found in dietary components and intermediate intermediates resulting from the heat breakdown of phenolic compounds, such as polyphenol-protein/starch compound complexes [23].…”
Section: Antioxidant Activity and Phenolic Totalsupporting
confidence: 75%
See 1 more Smart Citation
“…Another study discovered that cheese bread containing cowpeas had higher levels of condensed tannins, flavonoids, and total phenolic content. These results also align with the increase in antioxidant activity, which reached 497.5 and 731 µmol TEAC/100 gr using the DPPH and ABTS free radical scavenging methods [23] In addition, the components of the Maillard process in the crust increase the activity of bread. The antioxidant qualities of bread products can be impacted by phenolic compounds found in dietary components and intermediate intermediates resulting from the heat breakdown of phenolic compounds, such as polyphenol-protein/starch compound complexes [23].…”
Section: Antioxidant Activity and Phenolic Totalsupporting
confidence: 75%
“…These results also align with the increase in antioxidant activity, which reached 497.5 and 731 µmol TEAC/100 gr using the DPPH and ABTS free radical scavenging methods [23] In addition, the components of the Maillard process in the crust increase the activity of bread. The antioxidant qualities of bread products can be impacted by phenolic compounds found in dietary components and intermediate intermediates resulting from the heat breakdown of phenolic compounds, such as polyphenol-protein/starch compound complexes [23]. In line with the results of antioxidant activity analysis, total phenolic in bread samples also increased along with adding cowpea flour through the equation y = 5.3588x + 61.029 (R 2 = 0.9342).…”
Section: Antioxidant Activity and Phenolic Totalsupporting
confidence: 75%
“…Another study showed that enriching cheese bread with cowpea resulted in being a great source of calcium, phosphorous and magnesium (Cavalcante et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This study obtained 5.1 mg/100 g of iron (36.46% of RDI/adults) in a cereal bar prepared from texturized soy protein, wheat germ, oatmeal, and raisin banana. When compared to products with added cowpea, the B1 and B2 bars showed higher iron content than the biscuit (1.56 mg/100g), the swiss roll (1.16 mg/100 g) and the cheese bread (0.8 mg/100 g) developed by Frota et al (2010) and Cavalcante et al (2019), respectively.…”
Section: Mineralsmentioning
confidence: 76%